(untitled) (Abibisem: Journal of African Culture and Civilization, 2019)
The British Bank of West Africa (BBWA) now renamed Standard Chartered Bank Limited and Barclays Bank Ghana Limited were the two prominent foreign Commercial Banks first established in the Gold Coast in 1897 and 1917 respectively. In the colonial era, these British banks only dealt with large businesses and did not extend credit to individual Gold Coast farmers because they were tagged as not credit-worthy or could not arrange suitable collateral for loans. Essentially, lack of access to credit continues to be a key factor contributing to the poor performance of the agriculture sector in general.1 In 1953, the Ghana Commercial Bank (GCB) was established as the first indigenous commercial bank to serve the people of the nation.1 Since 1953, the Ghana Commercial Bank has made agriculture financing its priority and has extended loans to its agricultural customers. This paper, which is multi-sourced, uses archival documents, Government Records, Annual Reports and scholarly secondary works, to examine the approaches and strategies used by GCB to support agriculture in Ghana from the late 1960s to 1980s. The paper specifically sheds light on the measures adopted by the bank to transform agriculture in the country.